The development of an occupational therapy intervention for adults with a diagnosed psychotic disorder following discharge from hospital - Birken, Mary; Henderson, Claire; Slade, Mike (Biomed Central, 2018)
Background: A deterioration in mental health and admission to an acute mental health unit can result in skill loss and decreased participation in daily life. Furthermore, discharge from hospital is associated with high risks of social isolation and suicide. This intervention development study aims to describe the rationale, methods and processes of developing an intervention for adults with a diagnosed psychotic disorder following discharge from hospital. The intervention aims to increase participation in self-care and leisure, wellbeing and quality of life and reduce crisis service use. Methods: The United Kingdom Medical Research Council framework for the development of complex interventions was used to guide the process of developing the intervention to ensure the developed intervention is empirically justifiable and evidence based. The development involved a systematic and literature reviews and focus groups with people with psychosis and clinical staff to understand the problems the intervention should address and approaches to resolving these. Results: A manualised four-month intervention named Graduating Living skills Outside the Ward (GLOW) was developed for use by occupational therapists for people with a diagnosed psychotic disorder following discharge from hospital. The one-to-one stepped intensity intervention is of four months in duration and takes place in the person’s home and in community locations. The intervention aims to increase occupational performance of domestic and personal self-care, leisure and some productive roles. Conclusions: The intervention developed in this study has potential to improve the efficiency of community mental health services following discharge from hospital as it is evidence-based, time-limited and manualised and aims to reduce hospital admissions and crisis service use. The intervention will be tested to assess its clinical 41 and cost effectiveness in a randomised controlled trial.